Preoperative Survey of Patient’s, Understanding of Anaesthesia and the Role of Anaesthesiologists, Undergoing Elective Surgery, at an Urban Tertiary Care Hospital - Muhammad Zaid, Muhammad Saeed Siddiqui, Hannan Ayub, Sana Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of patients having adequate knowledge regarding anaesthesia and the role of anaesthesiologists. Study Design: Cross-sectional study. Place and Duration of Study: Department of Anaesthesiology & Critical Care, The Indus Hospital Karachi, Pakistan from 1stJanuary 2017 to 31stMarch 2018. Methodology: Patients presented to the preoperative anaesthesia clinic and or admitted in the hospital for elective surgeries. A pre-coded performa in national language (Urdu) was used for the evaluation of information regarding anaesthesia. Results: 95.1% had correct knowledge about general anaesthesia, 40.6% about local anaesthesia and 43.6% about regional anaesthesia. 71.8% replied that surgeon will determine whether patient is fit for surgery or not. 53% of the patients responded that surgeon will be responsible for the wellbeing of patients during surgery as compare to 36.1% according to whom anaesthetist is responsible for this. Conclusion: Poor understanding of anaesthesiologist’s role both inside and outside the operating room. Educational efforts should be continued, with the goal of alleviating general public’s knowledge regarding this life saving specialty. Keywords: Anaesthesia, Anaesthesiologist, Adequate knowledge